Hasil Belajar Siswa Melalui Model Pembelajaran Auditory, Itellectually, Repetition (AIR) Studi Eksperimen di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru - Muhammad Fikri; Gusma Afriani (Anotero Lembaga Scientific Pekanbaru, 2023)
This research aims to examine the effect of using the Auditory, Intellectually, Repetitive Learning Model on Student Learning Outcomes at Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. This research is a type of correlation research with a quantitative approach. The sample in this study was 60 people and sampling used simple random sampling. Data collection uses questionnaires, documentation and observation. The data analysis technique uses the product moment correlation test. The research results obtained r calculated 0.537 > r table at the 5% significance level (0.211) or at the 1% significance level (0.295), so Ha was accepted and H0 was rejected. This means that there is a positive influence of the use of the Auditory, Intellectually, Repetitive Learning Model on Student Learning Outcomes at Al-Muttaqin Madrasah Tsanawiyah Pekanbaru. The contribution of using the auditory, intellectually, repetitive learning model to student learning outcomes in the subject of Jurisprudence is 28.8%, while 71.2% influenced by other variables.